O que é isso companheiro?: um estudo sobre o gerenciamento da informação contábil nos municípios brasileiros - Tauk, Paulo Somesom (2012)
This study aims to identify whether the imposition of spending and borrowing limits by the Fiscal Responsibility Law ans the Transparency act influenced the practice of Earnings Management (GIC) by Brazilian municipalities. The punishment resulting from noncompliance with these standards is considered as sufficient incentive to the practice of the GIC. To identify these practices, the study used a modified version of the t-test, in order to analyze the distribution frequency of the relative difference between the economic value of the parameter studied and the actual value published by municipalities. The database includes the financial data for the year 2010 of 5212 municipalities, and enabled the analysis of six parameters: minimum expenditure on education, minimum expenditure on public health services, maximum consolidated personnel expenditures, maximum expenditures with municipal legislative offices, maximum revenue from credit operations in compared with current revenues and maximum revenue from credit operations compared to capital expenditures. The results showed evidence of earnings management for three of the six studied parameters: minimum expenditure on education, maximum expenditures with municipal legislative offices and maximum consolidated personnel expenditures. As major implications, there is the impact of the GIC in the reliability of information supplied by the Brazilian public sector, in view of the growing appreciation of transparency brought by recent legal innovations, such as the Access to Information Act.